Pengaruh Penerapan G-Suite bagi Perkembangan Pembelajaran di SMAN 1 Kalidawir Sidoarjo - Nurma Nabila; Elvira Intan Pramesti; Aris Sudaryanto (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
During the Covid-19 pandemic, the central government and regional governments must provide policies that can minimize the transmission rate and the Covid-19 virus. One of the central government's policies in dealing with the COVID-19 pandemic is to issue a policy for people to work or study from home. In this case, the government, namely the Ministry of Education and Culture, is collaborating with Google so that schools in Indonesia can still carry out learning using digital media and the internet through e-learning, namely using G-Suite for Education. One of the schools that uses G-Suite for Education is SMAN 1 Kalidawir Sidoarjo. However, the effect of applying G-Suite for learning development at SMAN 1 Kalidawir still needs to be measured. The research method of this article uses a qualitative descriptive method in which the source of information is related through the opinions of experts and qualified journals. The results of this article conclude that the application of G-Suite for Education greatly influences learning at SMAN 1 Kalidawir Sidoarjo to become a learning medium during a pandemic in which there are various features that can be used for bold learning to take place.